Single axis automatic tracking system based on PILOT scheme to control the solar panel to optimize solar energy extraction - Mostefa Ghassoul (Energy Reports, 2018)
Two types of solar panels are currently in use. Fixed panels; where they are placed at a convenient angle depending on the geographical location with a fixed tilt angle. But irradiation time merely exceeds six hours/day. The second type is rotating panels, either by continuously tracking the sun or through a preprogrammed angle at preprogrammed time. Unfortunately, both schemes, continuous tracking or pre-programmed are inefficient. In the first one, motor running at a very low speed requires a high torque which requires high current, leading to more driving power. In the second scheme, the system rotates at predetermined small angles independently whether the new position contributes to extra energy or not. In fact, it may have the opposite effect where all the extracted energy could be consumed by the driving system. This paper presents a new technique where those two draw backs have been addressed. The design uses a microcontroller-based control mechanism to maximize solar energy extraction. This is done by the design of a tracking system known as the PILOT and cells rotating system known as PANEL. First the system is oriented towards the east waiting for sun to rise. When this happens, the PILOT keeps tracking the sun. This is done with the aid of a light to frequency converter (LTF) mounted on a miniature electric motor. This converter always lines the PILOT with the sun. Two identical light dependent resistors (LDR) are mounted, one on the PILOT and the other on the PANEL. After each positioning of the PILOT, a comparison process takes over. If the voltage induced by the PILOT LDR is greater than that induced by the PANEL LDR plus a preset offset, the PANEL aligns itself with the PILOT, otherwise, it stays at its current position, and waits for the PILOT to move to new position, and the process repeats itself. By doing so, the PANEL only moves to the new location when the latter produces higher energy. At the end of the day, after sun set, the system returns to its initial position and waits for the following day.
Keywords: 330; LDR; LTF; PANEL; PIC microcontroller; PILOT; Solar cell